Thermoelectric properties of single-wall carbon nanotube networks. (24th June 2019) - Hayashi, Daisuke; Nakai, Yusuke; Kyakuno, Haruka; Hongo, Naoya; Miyata, Yasumitsu; Yanagi, Kazuhiro; Maniwa, Yutaka
Abstract: The Seebeck coefficient S and power factor P of single-wall carbon nanotube (SWCNT) networks were systematically investigated as a function of chemical potential μ, based on theoretical simulations employing non-equilibrium Green's function theory. The results focused on the gap regions of semiconducting (s-)SWCNTs. The thermoelectric properties of individual SWCNTs were classified into three groups: s-SWCNTs, metallic (m-)SWCNTs, and pseudo-metallic SWCNTs. The maximum values of P for individual s-SWCNTs was independent of SWCNT diameter. In parallel and serial networks of SWCNTs, S and P were found to be very sensitive to the amount of m-SWCNTs, as well as the SWCNT diameter distributions. A comparison with experimental results suggested that an SWCNT bundle can be modeled as a "rope" with an equivalent S calculated for parallel circuits. The presence of SWCNT junctions in the films substantially reduced the P value from those of the composing SWCNTs while S was almost unvaried.